Identification of Xanthine Oxidase Inhibitors in Single-Clove Black Garlic using Metabolomics and Molecular Docking Approaches - Setiawan, Abdul Aziz; Kumala, Shirly; Laksmitawati, Dian Ratih; Yuniarto, Ari; Yuliana, Nancy Dewi (UI Scholars Hub, 2025)
Black garlic is produced through controlled fermentation under specific temperature and humidity conditions, during which the Maillard reaction enhances its sensory properties and bioactivity. The anti-hyperuricemic potential of single-clove black garlic (SBG) remains unexplored. This study combined Ultra High-Performance Liquid Chromatography–High Resolution Mass Spectrometry-based metabolomics and an in-silico approach to identify the potential xanthine oxidase inhibitors (XOI) in SBG. Methanolic extracts (10 ppm) exhibited xanthine oxidase inhibition ranging from 50.09% to 68.01%, which is comparable to allopurinol (78.74%) at the same concentration. Metabolomic profiling tentatively identified 45 compounds, and orthogonal partial least squares analysis revealed seven metabolites as strongly correlated with XOI activity, namely α-(1-deoxy-D-fructose-1-yl)-L-arginine, alliin, 2-amino-2-deoxy-D-glucose, S-allyl-L-cysteine, quercetin, and m-coumaric acid. Molecular docking showed that these compounds exhibited binding energies comparable to allopurinol, thus indicating favorable interactions within the xanthine oxidase active site. Molecular dynamics simulations confirmed the stability of ligand–enzyme complexes, with consistent hydrogen bond interactions, which support their stable binding conformations. ADMET analysis revealed that most compounds demonstrated acceptable pharmacokinetic profiles, high intestinal absorption, low blood–brain barrier permeability, and non-hepatotoxic and non-mutagenic properties. The integration of metabolomics, molecular docking, molecular dynamics, and ADMET prediction supports the potential of SBG-derived compounds as safe and effective XOIs, thereby highlighting SBG as a promising functional food candidate for the management of hyperuricemia